The Regional Politics of Welfare in Italy, Spain and Great Britain - Vampa, Davide. author. aut Link
XVI, 259 p. 19 illus., 7 illus. in color.
Keywords: This book is a study of the increasing territorial variations in the development of sub-national welfare systems that have occurred as an effect of the decentralization of health care and social assistance policies in Italy, Spain and Great Britain. The author examines the political factors that underlie these variations by combining cross-regional and cross-country comparisons using mixed methods. Vampa’s main finding is that regionalist parties have played a key role in sub-national welfare building and have used social policy to strengthen their legitimacy in the political struggle against central authorities. In this context, functional political competition between Left and Right has been partly replaced by territorial competition between Centre and Periphery as the main determinant of social policy making. Additionally, mainstream left-wing parties have been torn between maintaining territorial uniformity in social protection and responding to demands for more extensive socialservices tailored to the needs and preferences of specific regional communities. This book will be of use to academics and policy makers interested in political economy, devolution/decentralisation, welfare, and party politics. .